Nitrogen enrichment buffers phosphorus limitation by mobilizing mineral-bound soil phosphorus in grasslands - Wang, Ruzhen; Yang, Junjie; Liu, Heyong; Sardans, Jordi; Zhang, Yunhai; Wang, Xiaobo; Wei, Cunzheng; Lü, Xiaotao; Dijkstra, Feike A.; Jiang, Yong; Han, Xingguo; Peñuelas, Josep (Ecology (Durham), 2022)
Phosphorus (P) limitation is expected to increase due to nitrogen (N)-induced terrestrial eutrophication, although most soils contain large P pools immobilized in minerals (Pi) and organic matter (Pₒ). Here we assessed whether transformations of these P pools could increase plant available pools alleviating P limitation under enhanced N availability. The mechanisms underlying these possible transformations were explored by combining results from a 10-year field N addition experiment and a 3700-km transect covering wide ranges in soil pH, soil N, aridity, leaching, and weathering that could affect soil P status in grasslands. Nitrogen addition promoted the dissolution of immobile Pi (mainly Ca-bound recalcitrant P) to more available forms of Pi (including Al- and Fe-bound P fractions and Olsen P) by decreasing soil pH from 7.6 to 4.7, but did not affect Pₒ. Soil total P declined by 10% from 385 ± 6.8 to 346 ± 9.5 mg kg−1, whereas available P increased by 546% from 3.5 ± 0.3 to 22.6 ± 2.4 mg kg−1 after the 10-year N addition, associated with an increase in Pi mobilization, plant uptake, and leaching. Similar to the N addition experiment, the drop in soil pH from 7.5 to 5.6 and increase in soil N concentration along the grassland transect were associated with an increased ratio between relatively mobile Pi and immobile Pi. Our results provide a new mechanistic understanding of the important role of soil Pi mobilization in maintaining plant P supply and accelerating biogeochemical P cycles under anthropogenic N enrichment. This mobilization process temporarily buffers ecosystem P limitation or even causes P eutrophication, but will extensively deplete soil P pools in the long run.